Alternative uses of functional finance: Lerner, MMT and the Sraffiansh - Ricardo de Figueiredo Summa (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
In the present paper, we will construct three comparable 'toy models' to evaluate the alternative uses of functional finance from Lerner, MMT, and the Sraffians. First, we will argue that the general functional finance framework can be separated from the specific views of Lerner on how the private sector and the economy works and its policy recommendations. Then, we use this separation to provide an alternative comparison between Lerner and the MMT to that proposed by Wray (2018), arguing that both agree with the general functional finance framework but disagree on how the private sector and the economy works, the policy objectives and the policy toolkit and recommendations. We argue that Lerner never abandoned his functional finance framework or his theoretical principles towards Monetarism. Finally, we will extend the same scheme to evaluate the functional finance framework from the Sraffian standpoint, motivated by recent attempts to check the compatibility of a specific Sraffian model - the supermultiplier - with functional finance (Skott et al, 2022, Fiebiger, 2021). The presentation of the three comparable 'toy models', by stressing the shared principles and specific disagreements between Lerner, MMT and the Sraffians allows us to discuss different policies and consequences of government's active role in promoting expansionary policies.
Keywords: E11; E12; E52; E62; 330; Functional finance; Abba Lerner; MMT; Sraffians; Macroeconomic policies